EthnoGRAPHIC: In Conversation with Manuel Ramos - Ramos, M. (EthnoGRAPHIC - Centre of Contemporary Arts - Glasgow, 2017)
nuel Ramos is a major figure in the worlds of both anthropology and graphic art. His journals of everyday life in Ethiopia and in Portugal develop various languages of analyses and exposition in the field, and his rich and detailed graphics are well known in Continental Europe and Africa, although still little known to English speaking readers. Recently, Ramos has been collaborating with fellow ethnographers in Brazil, Portugal and Scotland to advance debate and discussion of the discipline of graphic ethnography. In this special event, organised by The Drouth journal as part of the sketchday+festival, Ramos will speak with local graphic artist (and occasional ethnographer) and writer Mitch Miller about drawing in the field, capturing the moment and creating knowledge through both images and the word.